Changes in pharyngeal collapsibility and genioglossus reflex responses to negative pressure during the respiratory cycle in obstructive sleep apnoea. (15th January 2020) - Osman, Amal M.; Carberry, Jayne C.; Gandevia, Simon C.; Butler, Jane E.; Eckert, Danny J.
Abstract : Key points: Impaired pharyngeal anatomy and increased airway collapsibility is a major cause of obstructive sleep apnoea (OSA) and a mediator of its severity. Upper airway reflexes to changes in airway pressure provide important protection against airway closure. This study shows increased pharyngeal collapsibility and attenuated genioglossus reflex responses during expiration in people with OSA. Abstract: Upper airway collapse contributes to obstructive sleep apnoea (OSA) pathogenesis. Pharyngeal dilator muscle activity varies throughout the respiratory cycle and may contribute to dynamic changes in pharyngeal collapsibility. However, whether upper airway collapsibility and reflex responses to changes in airway pressure vary throughout the respiratory cycle in OSA is unclear. Thus, this study quantified differences in upper airway collapsibility and genioglossus electromyographic (EMG) activity and reflex responses during different phases of the respiratory cycle. Twelve middle‐aged people with OSA (2 female) were fitted with standard polysomnography equipment: a nasal mask, pneumotachograph, two fine‐wire intramuscular electrodes into the genioglossus, and a pressure catheter positioned at the epiglottis and a second at the choanae (the collapsible portion of the upper airway). At least 20 brief (∼250 ms) pressure pulses (∼−11 cmH2 O at the mask) were delivered every 2–10 breaths during four conditions: (1) early inspiration, (2) mid‐inspiration, (3) early expiration, and (4) mid‐expiration. Mean baseline genioglossus EMG activity 100 ms prior to pulse delivery and genioglossus reflex responses were quantified for each condition. The upper airway collapsibility index (UACI), quantified as 100 × (nadir choanal − epiglottic pressure)/nadir choanal pressure during negative pressure pulses, varied throughout the respiratory cycle (early inspiration = 43 ± 25%, mid‐inspiration = 29 ± 19%, early expiration = 83 ± 19% and mid‐expiration = 95 ± 11% (mean ± SD) P  < 0.01). Genioglossus EMG activity was lower during expiration (e.g. mid‐expiration vs . mid‐inspiration = 76 ± 23  vs . 127 ± 41% of early‐inspiration, P  < 0.001). Similarly, genioglossus reflex excitation was delayed (39 ± 11  vs . 23 ± 7 ms, P  < 0.001) and reflex excitation amplitude attenuated during mid‐expiration versus early inspiration (209 ± 36  vs . 286 ± 80%, P  = 0.009). These findings may provide insight into the physiological mechanisms of pharyngeal collapse in OSA. Key points: Impaired pharyngeal anatomy and increased airway collapsibility is a major cause of obstructive sleep apnoea (OSA) and a mediator of its severity. Upper airway reflexes to changes in airway pressure provide important protection against airway closure. This study shows increased pharyngeal collapsibility and attenuated genioglossus reflex responses during expiration in people with OSA.